Hubungan Kemampuan Berpikir Kritis dan Kemampuan Berpikir Kreatif pada Pembelajaran IPA di Sekolah Dasar: The Relationship Between Critical Thinking Ability and Creative Thinking Ability in Science Learning in Elementary School - Wahyu Karisma Wati; Prima Mutia Sari (Tunas: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
Critical thinking and creative thinking skills are skills that are in high demand in the 21st century. Many assume that these skills can be developed simultaneously, so that children who are able to think critically are considered capable of creative thinking as well. Therefore, this study aims to see the relationship between these skills. This study used quantitative methods with a correlational approach, with data collection techniques using tests. The test instruments used in this study are tests of critical thinking skills in indicators of interpretation, analysis, evaluation and inference. While the test of creative thinking skills on indicators of fluency, flexibility, elaboration and originality. The population in this study was all grade V of Assisted Elementary School 2 Cluster 6 Ciracas District as many as 16 classes and the sample of the study was 4 classes. The sampling technique was cluster random sampling. The correlation test results showed a relationship between critical and creative thinking skills. Furthermore, the results of the regression coefficient showed a value of 0.999, meaning that critical thinking skills affect 99% of creative thinking abilities.